Social dialogue, working time arrangements and work-life balance in European companies - Kümmerling, Angelika; Lehndorff, Steffen (Dublin, 2009)
"Working time policies, although designed within the national and sectoral framework and the boundaries of institutional regulations, are fine-tuned and implemented at the level of each company, taking account of the environment in which the company operates and the workforce it is employing. Hence, companies have placed more importance on working time organisation in recent years. In light of this, the European Foundation for the Improvement of Living and Working Conditions launched in 2004 its first Establishment Survey on Working Time and Work–Life Balance (ESWT), covering a large array of working time arrangements such as flexible working hours, overtime, part-time work, work at unusual hours, childcare leave or other forms of long-term leave, and phased or early retirement."